2017
DOI: 10.1021/acs.jpcc.7b04418
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Kinetics in the Process of Reduction of Nanocrystalline Iron Nitride γ′-Fe4N

Abstract: The kinetics of the reduction of nanocrystalline γ′-iron nitride to α-iron in mixtures of nitrogen and hydrogen of different hydrogen concentration was studied. Kinetic measurements were carried out in a differential chemical reactor with a thermogravimetric system for measuring the weight of a sample and an analyzer of hydrogen at 400 °C and at atmospheric pressure. The occurrence of cyclic changes in the rate of chemical reaction in a solid phase has been observed. Such an oscillatory phenomenon was not obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Saraev et al [42] observed oscillatory phenomena in solid-phase-gas-phase reaction systems with phase transformation of a solid substrate in the surface layer (a range of several dozens of atomic layers). As a result of detailed kinetic studies of the nitride reduction process, we observed oscillatory changes in the rate of the reduction reaction of iron γ'-Fe 4 N iron nitride to α-iron [43]. The observed oscillatory phenomenon has been explained by a gradual variation in the free enthalpy of nitrogen segregation.…”
Section: Introductionmentioning
confidence: 82%
“…Saraev et al [42] observed oscillatory phenomena in solid-phase-gas-phase reaction systems with phase transformation of a solid substrate in the surface layer (a range of several dozens of atomic layers). As a result of detailed kinetic studies of the nitride reduction process, we observed oscillatory changes in the rate of the reduction reaction of iron γ'-Fe 4 N iron nitride to α-iron [43]. The observed oscillatory phenomenon has been explained by a gradual variation in the free enthalpy of nitrogen segregation.…”
Section: Introductionmentioning
confidence: 82%
“…Room temperature soft-magnets are materials that quickly respond to changes in external magnetic fields at room temperature and can obtain high magnetization with low loss. They have important applications in power transformers, high frequency inductors, electric motor rotors, flux gate magnetometers, and high-density recorders [13][14][15][16]. There are two different types of Fe atoms in the γ -Fe 4 N unit cell.…”
Section: Introductionmentioning
confidence: 99%